Upgrading OTOP Community Products by Blue Ocean Marketing Strategy for Beverage Products - Satabodee, Chonlakan (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2022)
The objectives of this research are to study the current management of OTOP product community entrepreneurs for beverage products and to find ways to upgrade OTOP products community by using blue water marketing strategy for beverage products. This research is a qualitative research using descriptive data analysis. Structured interview was used to collect data. The in-depth interview was conducted with entrepreneurs which the samples were obtained from the database of entrepreneurs of the Provincial Community Development Offices, Provincial Commercial Offices, Provincial Public Health Offices and Provincial Industrial Offices in the area 14 of southern provinces, selected by purposive sampling. The 2 OTOP products per province were selected, using criteria in 3 areas: (1) strengthening communities products, (2) marketing and (3) product background. Entrepreneurs with a product rating less than 3 stars which was capable of reaching to 3-star level as well as those with product with a 2-star rating, were selected as a sample group for in-dept interviews; key informants and casual informants included 42 people in total. The results showed that current management of OTOP beverage products was found using 2 methods: 1) management process and 2) organizational environment analysis. In term of using blue ocean marketing strategies for beverage products, it can be divided into 3 methods: (1) changing employee attitudes, (2) knowing customer needs, and (3) creating new demands with innovation.